The Effect of Learning Independence on Arabic Learning Achievement at SDI Terpadu Al-Khairaat Yogyakarta - Ikhwan Nur Rois; Sarah Almaulidia (JENIUS (Journal of Education Policy and Elementary Education Issues), 2023)
Learning achievement determines the achievement of a learning objective. One of the factors that affect student achievement is learning independence. Learning independence is one of the important aspects for individuals to regulate their learning process. However, learning Arabic, carried out online, showed low student achievement. Hence, this study aimed to determine the relationship and influence of learning independence on student achievement. The study was conducted at SDI Terpadu Al-Khairat Yogyakarta in February 2022 with a population of 69. The sampling technique uses simple random sampling with a total of 59 students. The data collection instrument uses questionnaires for self-reliance in learning with 3 aspects: emotional, behavioural, and value independence. The number of questionnaire items is 34, consisting of 31 items declared valid and reliable. Based on the linearity results, it shows a significance of 0.602 > 0.05, which can be concluded that there is a linear relationship, while based on the normality test, the data is not normally distributed. The results of the hypothesis test showed a significance level of 0.344 > 0.05, so it can be concluded that learning independence has no significant influence on learning achievement. The effect of learning independence on learning prevalence was 1.6%, while other factors influenced 98.4%.